Management of complicated multirecurrent pterygia using multimicroporous expanded polytetrafluoroethylene. Issue 6 (15th March 2013) - Kim, Kyoung Woo; Kim, Jae Chan; Moon, Jun Hyung; Koo, Hyun; Kim, Tae Hyung; Moon, Nam Ju
Abstract : Aims: To evaluate the efficiency of multimicroporous expanded polytetrafluoroethylene (e-PTFE) insertion in complicated multirecurrent pterygia. Methods: A total of 62 eyes from 62 patients with a multirecurrent pterygium associated with symblepharon or motility restriction-related binocular diplopia were recruited. All eyes underwent pterygia excision followed by application of 0.033% mitomycin C, amniotic membrane transplantation and conjunctival limbal autograft. Multimicroporous e-PTFE was then inserted intraoperatively in 30 eyes between the transplanted amniotic membrane and the conjunctiva (group A), but not inserted in the other 32 eyes (group B). The main outcome measures were symblepharon formation, motility restriction, binocular diplopia, subjective score of conjunctival hyperaemia and postoperative pterygium recurrence. Results: In the mean follow-up period of 17.2±2.3 months, symblepharon formation, motility restriction, diplopia and conjunctival hyperaemia were significantly improved after surgery in group A patients (p=0.000, 0.000, 0.008 and 0.000, respectively). Postoperative symblepharon formation, motility restriction and conjunctival hyperaemia were significantly less in group A compared to group B (p=0.024, 0.027 and 0.000, respectively). After surgery, corneal recurrence developed in one eye (3.3%) from group A, which was significantly lower than the eight eyes (25%) from group B (p=0.027). Conclusions: Multimicroporous e-PTFE insertion may provide a novel approach for treating intractable complicated multirecurrent pterygia.